Identifying student conceptual resources for understanding physics: A practical guide for researchers - Amy D. Robertson; Lisa M. Goodhew; Lauren C. Bauman; Brynna Hansen; Anne T. Alesandrini (Physical Review Physics Education Research, 2023)
[This paper is part of the Focused Collection on Qualitative Methods in PER: A Critical Examination.] Identifying student ideas about particular physics topics is one of the earliest and longest-standing foci of physics education research. This paper presents a method for identifying common conceptual resources for understanding physics, using large numbers of written student responses to conceptual questions. We walk researchers step by step through how we have done this ourselves, from collecting data, to identifying candidate resources, to turning our lists of candidate resources into a coding scheme that can then be applied to datasets of >200 responses. The outcome of these methods are lists of common conceptual resources for understanding particular topics in physics, such as forces, energy, circuits, and heat and temperature.